Housing sows after weaning: re-establishment of estrus and subsequent reproduction - W E Schmidt; Duane L Davis; Jeffrey S Stevenson (Kansas Agricultural Experiment Station Research Reports, 1983)
We penned sows after weaning either in groups of 4 or 5 or individually in gestation stalls. Beginning 3 days after weaning sows were checked twice daily and artificially inseminated 24 and 36 hr after first detected estrus. Twenty four to 48 hr after their last insemination sows either were moved to the other penning treatment, or remained in their weaning treatment, for 30 additional days. Group penning after weaning resulted in a slightly shorter interval to estrus (.25 day; P<.05). But percent sows in estrus by 10 days after weaning was similar in both groups. No effects on farrowing rate or litter size, due to weaning treatment, were observed. Post-breeding treatment affected farrowing rate (P<.05) with 80.6% of sows penned in groups farrowing, as opposed to 67.3% of individually stalled sows. No effects on either total or Iive pigs farrowed could be attributed to post-breeding treatment.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Estrus; Reproduction; Housing; Weaning; Sows